Electronic Structure of Nitrobenzene: A Benchmark Example of the Accuracy of the Multi-State CASPT2 Theory - Algarra-González, Manuel; Soto-Martín, Juan (ACS Publications, 2021)
The electronic structure of nitrobenzene (C6H5NO2) has been studied by means of the complete active space self-consistent field (CASSCF) and multi-state second-order perturbation (MS-CASPT2) methods. To this end, an active space of 20 electrons distributed in 17 orbitals has been selected to construct the reference wave function. In this work, we have calculated the vertical excitation energies and the energy barrier for the dissociation of the molecule on the ground state into phenyl and nitrogen dioxide. After applying the corresponding vibrational corrections to the electronic energies, it is demonstrated that the MS-CASPT2//CASSCF values obtained in this work yield an excellent agreement between calculated and experimental data. In addition, other active spaces of lower size have been applied to the system in order to check the active space dependence in the results.
Keywords: Disociación; Estructura electrónica; CASSCF; Reacción de Disociación; Nitrobenceno